2020
DOI: 10.1186/s12920-020-0687-0
|View full text |Cite
|
Sign up to set email alerts
|

Pseudogene-gene functional networks are prognostic of patient survival in breast cancer

Abstract: Background: Given the vast range of molecular mechanisms giving rise to breast cancer, it is unlikely universal cures exist. However, by providing a more precise prognosis for breast cancer patients through integrative models, treatments can become more individualized, resulting in more successful outcomes. Specifically, we combine gene expression, pseudogene expression, miRNA expression, clinical factors, and pseudogene-gene functional networks to generate these models for breast cancer prognostics. Establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Pseudogene-gene interaction between GPS2-GPS2P1 is prognostic even though neither the gene nor the pseudogene alone is prognostic of survival. miR-3923 was predicted to target GPS2 using miRanda, PicTar, and TargetScan, implying modules of gene-pseudogene-miRNAs that are potentially functionally related to patient survival [86]. Pseudogene HLA-DPB2 and its parental gene HLA-DPB1 are overexpressed and correlated with better BC patient prognosis.…”
Section: Cancers Located In the Chest Areamentioning
confidence: 99%
“…Pseudogene-gene interaction between GPS2-GPS2P1 is prognostic even though neither the gene nor the pseudogene alone is prognostic of survival. miR-3923 was predicted to target GPS2 using miRanda, PicTar, and TargetScan, implying modules of gene-pseudogene-miRNAs that are potentially functionally related to patient survival [86]. Pseudogene HLA-DPB2 and its parental gene HLA-DPB1 are overexpressed and correlated with better BC patient prognosis.…”
Section: Cancers Located In the Chest Areamentioning
confidence: 99%
“…For this study, the decision tree described factors such as having an endoscopic/biopsy procedure and vomiting symptom with the most probable pathway to NET diagnosis. Conditional interference trees have been previously used to identify characteristics associated with infarct growth rate and neurologic disability among ischemic stroke patients and to identify predictors of breast cancer survival [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Smerekanych et al conducted a systematic identification of gene expression, pseudogene expression, miRNA expression, and pseudogene-gene interactions and clinical factors that were predictive to breast cancer patients' prognosis [17]. Based on a regression model with L1 penalty, the authors identified the over expression of STXBP5, GALP and LOC387646, the up regulation of pseudogene CTSLP8 and RPS10P20 and down regulation HLA-K, the pseudogene-gene interaction between GPS2 and GPS2P1, and the microRNA miR-3923 were significantly associated with the overall survival of breast cancer.…”
Section: Biomarker Predictionmentioning
confidence: 99%